(untitled) (UNED Research Journal, 2016)
Fishing communities often face similar challenges that include overfishing, lack of food security, and unenforced sustainability policies. Tárcoles, mid-Pacific coast of Costa Rica, generates the majority of its income through fishing. A local cooperative aids families with direct marketing, lowering middleman power and generally benefitting the community. To understand the role of the shrimp Litopenaeus vannamei, we interviewed 47 women and youth (aged 13-72) and 41 young students (17-24) at the University of Costa Rica. We found that shrimp is a vital resource used both for food security and to improve economic situations of fishermen and women. People who have been fishing for more years perceive more positively the success of conservation efforts (P=0,05). Fishermen who have fished in more recent years also perceived greater success in shrimp recuperation in the town (P=0,03). At the University of Costa Rica, many students had at least a basic awareness of social and economic realities in rural fishing communities. Knowledge about artisanal fishing from UCR students was found to be very limited, with many respondents believing that artisanal fishing communities have no impact on large cities in Costa Rica. They should receive more education on this subject.